PENDAMPINGAN PENDIRIAN DAN OPERASIONAL BANK SAMPAH PELATIHAN PENGOMPOSAN DI LIMA DUSUN DESA BANJARANGKAN KABUPATEN KLUNGKUNG BALI - Ciawi, Y.; Dwipayanti, N.M.U.; Wrasiati, L.P.; Purnama, G.H.; Pharmawati, M. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This program aims to overcome the waste problem in Banjarangkan Village, Klungkung Regency in order to comply with Bali Governor Regulation no. 47 of 2019. The activity begins with a visit to the village, reviewing the existing local waste processing unit, determining the date of the activity, preparing tools and equipment, socialization of household waste management, set up the waste bank, training on composting, constructing biopore holes and wells. The socialization of household waste management was carried out in September 2021 at the village office, attended by all waste bank officers, the head of the village and other officials. On September 9, the first opening of Waste Banks was held in Dusun Nesa and Koripan and Koripan Tengah and on September 10, 2021, in Dusun Selat and Pagutan. On October 7, 2021, training on household waste management and composting was held in Banjar Pagutan, Banjarangkan. Meanwhile, the construction of biopori wells and biopori holes was carried out in the house of one of the residents as a pilot with the aim that when it was successful, the village could continue and duplicate the activities. The same wells were also constructed in SMPN 1 Banjarangkan. Keywords: Banjarangkan, segregation, trash bank, composting, biophore well